Phylogenetic and Genome Analysis of 17 Novel Senecavirus A Isolates in Guangdong Province, 2017 - Sun, Yuan; Cheng, Jian; Wu, Rui-Ting; Wu, Zi-Xian; Chen, Jun-Wei; Luo, Ying; Xie, Qing-Mei; Ma, Jing-Yun (Frontiers in Veterinary Science, 2018)
Senecavirus A (SVA), an emerging RNA virus, is considered to be associated with porcine idiopathic vesicular disease (PIVD). From February to September 2017, 17 novel Senecavirus A (SVA) strains were isolated from samples with the vesicular disease from Guangdong Province, China. Full-length genomes of the 17 new SVA isolates were genetically and phylogentically analyzed. Results showed that these 17 novel SVA isolates revealed 96.5% to 99.8% nucleotides identities with each other and separated in three well-defined groups. Phylogenetic analysis for all available Chinese SVA strains indicated that 45 Chinese SVA strains clustered into five distinct groups with no significant relationship between strains from different provinces and/or years, including a newly emerging branch in China. This is the first comprehensive study of phylogenetic analysis for all available Chinese SVA strains, indicating the appearance of a new type of SVA strains and the complicated circulations with at least five different types of SVA strains in pigs in China.